2016
DOI: 10.1103/physrevlett.116.063002
|View full text |Cite
|
Sign up to set email alerts
|

Strong Field Molecular Ionization in the Impulsive Limit: Freezing Vibrations with Short Pulses

Abstract: We study strong-field molecular ionization as a function of pulse duration. Experimental measurements of the photoelectron yield for a number of molecules reveal competition between different ionization continua (cationic states) which depends strongly on pulse duration. Surprisingly, in the limit of short pulse duration, we find that a single ionic continuum dominates the yield, whereas multiple continua are produced for longer pulses. Using calculations which take vibrational dynamics into account, we interp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 51 publications
2
36
0
Order By: Relevance
“…The ponderomotive potential is estimated to be approximately 0.5-0.7 eV based on previous work [24,29]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The ponderomotive potential is estimated to be approximately 0.5-0.7 eV based on previous work [24,29]. …”
Section: Resultsmentioning
confidence: 99%
“…In our previous work studying CH 2 IBr, we found that vibrational dynamics and nonadiabatic transitions following resonant excitation of the neutral molecule could be suppressed by using laser pulses with a duration shorter than the vibrational period [24]. By making the pulses sufficiently short (<10 fs), we were able to "freeze out" the nuclear motion, preventing population transfer via nonadiabatic coupling, resulting in ionization to only a single state of the cation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…III that along the nuclear coordinate which largely describes the motion on D 0 and D 1 after ionization, there are 1-photon resonances in CH 2 IBr near the FC while there is only one 2-photon resonance in CF 3 I that is far away from the FC. We note that the relative change in the D 0 and D 1 yields with pulse duration is due to non-adiabatic dynamics in intermediate neutral states, which we considered in a separate study [25].…”
Section: % Of the Yield In These Experiments) Solid Lines Are Measmentioning
confidence: 99%